(untitled) (Herald of Journalism, 2016)
100 years from the date of a release of the newspaper «Kazak» which occupied a special role in public life and in historical development of the Kazakh people at the beginning of the XX century were executed. It is known that the newspaper was issued on February 2, 1913 in the city of Orenburg from «Karimovs, Husainov’s Printing house». The greatest part of the Kazakh intellectuals which openly supported national liberation and political struggle against colonizer policy of imperial Russia and actively fought for freedom and independence of the people, all of them rallied round the newspaper «Kazak» (1913-1918).